Performance of State Corporations in Kenya: The Role of Electronic Supplier Relationship Management - Linus Ndege Murithi; Patrick Karanja Ngugi; David Kiarie (Integrasi Sains Media, 2024)
This paper aims to examine the relationship between electronic supplier relationship management (e-SRM) and the performance of state corporations in Kenya. Effective management of supplier relationships is crucial for enhancing suppliers' contributions to organizational performance. However, the adoption of electronic means for managing these relationships has been insufficiently explored, particularly in the public sector. The study focused on all 248 state corporations in Kenya, from which a sample of 153 corporations was selected using a stratified random sampling technique. Employing a descriptive correlational research design, primary data were collected through questionnaires and analyzed using both descriptive and inferential statistics. The findings indicate a significant relationship between electronic supplier relationship management and the performance of state corporations in Kenya (? = 0.843, P = 0.0001 < 0.05). The study concludes that the persistent underperformance of state corporations is significantly linked to the limited adoption of electronic supplier relationship management practices. Therefore, it is recommended that state corporations, through their senior management, including heads of procurement and supply chain, integrate electronic supplier relationship management to streamline their supplier relationships and enhance overall performance.